2017
DOI: 10.24953/turkjped.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sleep in pediatric cancer patients

Abstract: İnce D, Demirağ B, Karapınar TH, Oymak Y, Ay Y, Kaygusuz A, Töret E, Vergin C. Assessment of sleep in pediatric cancer patients. Turk J Pediatr 2017; 59: 379-386. The purpose of the study is to describe sleep habits, assess the prevalence of sleep disturbances in pediatric cancer patients and healthy controls, and to compare sleep patterns, sleep problems. One hundred-thirty-five patients and 190 healthy controls were evaluated. Healthy children matched for age, sex, economic status, parental education and fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Academic performance decreases as sleep quality and duration decline. On the other hand, Unalan et al [36] reported an inversely proportional relationship between sleep duration and academic performance, with improved performance as real sleep time decreased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Academic performance decreases as sleep quality and duration decline. On the other hand, Unalan et al [36] reported an inversely proportional relationship between sleep duration and academic performance, with improved performance as real sleep time decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Short sleep times were associated with reduced academic performance. In contrast, Unalan, Orturk, Ismaliogullari, Akgul, and Aksu [36] established that sleep duration was inversely related to student performance, with longer sleep being related to poorer academic performance. Dewald, Meijer, Oort, Kerkhof, and Bögels [37] determined the existence of a significant relationship between sleep and performance in children and adolescents, the less often they woke up in the night, the better their performance, and the longer they slept, the better their performance.…”
Section: Associations Between Academic Performance and Sleepmentioning
confidence: 93%
See 1 more Smart Citation
“…However, questionnaires do not measure sleep duration and sleep efficiency, and do not correlate well with polysomnography, the gold standard for measuring sleep 15 . Some questionnaire studies only assess parent-reported sleep 16,17 , and this inherently poses some reporting bias. Using several modes of sleep assessment is important as it provides complementary information and contributes to our understanding of sleep 15,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Children with hematological and oncological diseases are at a high risk of developing sleep disorders. 1 Besides treatment for malignancies affecting sleep behaviors in children, 1,2 adult survivors of childhood cancer are known to develop fatigue and poor sleep, 3 -5 causing behavioral and neurocognitive impairment. However, studies have focused on insomnia and hypersomnia, and non–rapid eye movement (NREM)–related parasomnias, which are very common in children aged 3 years or more, 6,7 have rarely been studied among children undergoing treatment for cancer.…”
mentioning
confidence: 99%